Quantum dissipation and phenomenological approache - Chattah, A.K.; Caceres, M.O. (Condensed Matter Physics, 2000)
Using Terwiel’s cumulants the Markovian approximation to arrive to the Quantum Master Equation, for a system interacting with a thermal bath, is revisited. The second order weak coupling approximation is analyzed, then a Kossakowski-Lindblad form for the generator is written in terms of the position and momentum operators. A weak coupling approximation for the stochastic non-Markovian wave function is worked out. A free particle model interacting with a thermal quantum bath is studied in the context of Schrödinger-Langevin picture. A phenomenological point of view is introduced in order to overcome certain difficulties in the time evolution – in the second order approximation – for the free particle Hamiltonian.